The relationship between evolving sarcopenia and efficacy of immune checkpoint inhibitor in non‐small cell lung cancer patients. Issue 4 (15th July 2021) - Makiguchi, Tomonori; Tanaka, Hisashi; Taima, Kageaki; Tatsuo, Soichiro; Iida, Saya; Kakeda, Shingo; Tasaka, Sadatomo
Abstract: Background: Sarcopenia has been receiving attention in the cancer field. We investigated whether evolving sarcopenia is associated with the outcome of non‐small cell lung cancer (NSCLC) patients receiving immune checkpoint inhibitors (ICIs). Methods: In this retrospective study, 46 NSCLC patients who received ICIs were subjected. Skeletal muscle area at the level of the third lumbar vertebra (L3‐SMA) was measured from CT images taken before and 90 days after the ICI treatment. The efficacy‐related factors were determined by logistic regression analysis. The prognostic cut‐off value was estimated by a receiver operating characteristic (ROC) curve. Area under curve (AUC) was evaluated. Covariate factors included age, gender, smoking history, histology, performance status, PD‐L1 tumour proportion score, status of driver mutations, body mass index, serum total protein, albumin levels, and peripheral lymphocyte count. Progression free survival (PFS) and overall survival (OS) analysis were conducted by Kaplan–Meier method. Data cut off was determined to be 700 days. Results: Patient characteristics in age (mean ± SD) and gender (male, %) were 65.5 ± 9.2 years old and 80.4%. In the multivariate analysis, only reduction rate of L3‐SMA was significant (odds ratio 1.14, P = 0.02). The cut‐off value was estimated to be 6% (AUC 0.84, P < 0.0001). Median PFS of patients with L3‐SMA over 6% and those with less was 2.4 and 15.7 months, respectively ( P < 0.0001). As for OS, the median time was 10.0 months versus not reached ( P = 0.012). Conclusions: Evolving sarcopenia assessed with CT images could be a promising prognostic factor in NSCLC patients receiving ICIs.